A FEMINIST STYLISTIC ANALYSIS: WOMEN LEADERSHIP OF LITTLE MIX FEAT NICKI MINAJ’S LYRICS SONG WOMEN LIKE ME - Simanjuntak, Windy Octalin; Saragih, Silvia Efani; Sihotang, Tiarma; Rangkuti, Rahmadsyah (Universitas Gunadarma, 2024)
This study utilized a feminist approach, specifically feminist stylistics based on Mills’s theory, to describing how women leadership presented in song lyrics. The researchers analysed the lyrics of the song Women Like Me by Little Mix feat Nicki Minaj as the primary source of the study. The data were descriptive qualitative using techniques such as data reduction, data display, and conclusion drawing or verification. The findings of the study focused on stylistic analysis at the word level, at the phrase and sentence level, and at the discourse level. The research identified women leadership tendencies in language use, where certain words or phrase were exclusively associated with women. Actually, women were more commonly described based on their overall appearance. This study suggests further exploration of feminist stylistics to better understand the impact of feminism on individuals’ live.